THE INFLUENCE OF RELATIONAL MARKETING AND EXPERIENTIAL MARKETING ON PATIENT LOYALTY WITH PSYCHOLOGICAL FACTORS AS A MODERATION VARIABLE IN OUTPATIENTS OF BHAKTI KARTINI HOSPITAL BEKASI - Alawiyah, Tuti; Ramadhan, Yanuar (PT Altin Riset Publishing, 2025)
Patient loyalty is a major challenge for hospitals, including Bhakti Kartini Hospital Bekasi, which face intense competition in the health industry. This problem arises because there will be a decrease in the number of old and new patients in 2023. This is due to the lack of strong relationships between hospitals and patients, as well as inadequate patient experience. This research aims to analyze the influence of relationship marketing and experiential marketing on patient loyalty, with psychological factors as moderating variables. The research method used is quantitative with a cross-sectional study design. Data was collected from 170 outpatient respondents through a questionnaire consisting of questions related to relationship marketing, experiential marketing, psychological factors and patient loyalty. Data analysis was carried out using SEM-PLS. The research results show that relationship marketing, experiential marketing and psychological factors have a significant influence on patient loyalty both simultaneously and partially. In addition, psychological factors are proven to moderate the relationship between these two variables, thereby increasing the impact of relationship marketing and experiential marketing on patient loyalty. The implications of these findings demonstrate the importance for hospitals to develop communication systems and marketing strategies that focus on long-term relationships with patients and creating positive experiences. In this way, Bhakti Kartini Hospital can increase patient loyalty and strengthen its position in the health industry.